2009
DOI: 10.1159/000236355
|View full text |Cite
|
Sign up to set email alerts
|

Total and Fetal Cell-Free DNA Analysis in Maternal Blood as Markers of Placental Insufficiency in Intrauterine Growth Restriction

Abstract: Objective: To compare total and fetal DNA levels in the maternal plasma in three groups: pregnancies with intrauterine growth restriction (IUGR) due to placental insufficiency (PI) and other causes, and in control pregnancies. Methods: Total as well as fetal DNA was quantified in 78 maternal plasma samples. In 19 pregnancies, the fetus presented IUGR due to PI (group A), and in 31 pregnancies due to other causes (group B). The control group comprised 28 patients (group C). DNA quantification was done using rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 70 publications
2
27
3
1
Order By: Relevance
“…Distinguishing the cause of IUGR is likely important, as an increase of cfp-DNA levels was previously observed only for those IUGR cases associated with PE [37] . In cases of IUGR in twins, the cfp-DNA level was increased consistent with a cumulative effect of multiple gestations [27] and, possibly, placental lesions [38] .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Distinguishing the cause of IUGR is likely important, as an increase of cfp-DNA levels was previously observed only for those IUGR cases associated with PE [37] . In cases of IUGR in twins, the cfp-DNA level was increased consistent with a cumulative effect of multiple gestations [27] and, possibly, placental lesions [38] .…”
Section: Discussionmentioning
confidence: 95%
“…Besides the high variability of controls, nondiscriminatory levels of cfp-DNA in GH cases can also be explained by (i) a nonlinear elevation before onset of symptoms [35,36] and (ii) different levels of elevation in different subtypes of PE [26,37] .…”
Section: Discussionmentioning
confidence: 99%
“…The cfp-DNA levels in IUGR were found to be either normal or increased but to a lesser extent than early-onset PE. 51, [85][86][87] Moreover, when IUGR cases were subdivided according to the presence or absence of PE, only the PE-related IUGR group revealed a significant cfp-DNA increase. 85 Increased FLT-1 protein level in placenta and maternal blood is well established to be associated with PE and IUGR.…”
Section: Preeclampsiamentioning
confidence: 93%
“…51, [85][86][87] Moreover, when IUGR cases were subdivided according to the presence or absence of PE, only the PE-related IUGR group revealed a significant cfp-DNA increase. 85 Increased FLT-1 protein level in placenta and maternal blood is well established to be associated with PE and IUGR. Likewise, increased FLT-1 mRNA was detected in the plasma of nonhypertensive women with IUGR fetuses (<2 SD of mean fetus size) as early as the first trimester.…”
Section: Preeclampsiamentioning
confidence: 93%
“…In the first research (16), authors did not find any discrepancy between cfDNA concentrations in cases of normal pregnancies and the ones with IUGR. Later studies indicated that cfDNA concentrations are increased in cases of pregnancies with IUGR (18)(19)(20)(21). It is of importance that in these studies the authors did not take into account the processes of elimination of cfDNA from plasma.…”
Section: Introductionmentioning
confidence: 99%